Thermoluminescence properties of nano-alumina with two different particle sizes - Mammadov, S.; Gurbanov, M.; Ahmadzade, L.; Abishov, A. (Physics and Chemistry of Solid State, 2023)
This research aims to examine the thermoluminescence (TL) properties of nano-sized alumina, including the relationship between TL intensity and absorbed dose, the identification of individual luminescence peaks, and determining trap parameters for use as a possible dosimeter. The samples were exposed to 530 to 2646 Gy doses from 60Co irradiation. The results show that micro-sized α-Al2O3 had a main dosimetry peak at Tm = 435 K, while nano-α-Al2O3 samples with particle sizes of 40 and 50 nm displayed a TL luminescence glow curve, with the primary dosimetry peak located in the low-temperature range and a complex structure at higher temperatures (above 500 K). The primary dosimetry peak was influenced by nanoparticle size, with a maximum of 460 K for the 40 nm sample and 467 K for the 50 nm sample. The main dosimetry peak was described by the superposition of two peaks